2009
DOI: 10.1038/ni.1761
|View full text |Cite
|
Sign up to set email alerts
|

The impact of negative selection on thymocyte migration in the medulla

Abstract: Developing thymocytes are screened for self-reactivity before exiting the thymus, but how thymocytes scan the medulla for self-antigens is unclear. Using two-photon microscopy, we observed that medullary thymocytes migrated rapidly and made frequent, transient contacts with dendritic cells. In the presence of a negative selecting ligand, thymocytes slowed, became confined to areas of approximately 30 microns in diameter, and had increased contact with dendritic cells surrounding confinement zones. One third of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
126
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 39 publications
15
126
0
Order By: Relevance
“…High motility is a consistent feature of SP thymocytes in the medulla (6,25,34,35) and mature T cells in lymph nodes (36), implying that increased motility reflects long-lasting changes in the cellular machinery that controls migration, rather than a short-term response to a chemokine gradient. Consistent with this notion, gene-expression studies of pre-and postselection DP thymocytes revealed induction of numerous genes that may play a role in regulating cell adhesion, metabolism, and the cytoskeleton (37)(38)(39).…”
Section: Discussionmentioning
confidence: 97%
“…High motility is a consistent feature of SP thymocytes in the medulla (6,25,34,35) and mature T cells in lymph nodes (36), implying that increased motility reflects long-lasting changes in the cellular machinery that controls migration, rather than a short-term response to a chemokine gradient. Consistent with this notion, gene-expression studies of pre-and postselection DP thymocytes revealed induction of numerous genes that may play a role in regulating cell adhesion, metabolism, and the cytoskeleton (37)(38)(39).…”
Section: Discussionmentioning
confidence: 97%
“…One possible explanation for this could be that the requirements for scanning and pMHC contacts are less stringent for negative selection than for positive selection. Negative selection in the medulla requires regulation of thymocyte migration patterns (7,33), and thymocytes spend about twice as much time undergoing negative selection (4-5 d) than positive selection in the cortex (2-3 d) (34). If the increased migration of aPix 2 thymocytes results in inefficient, error-prone scanning for pMHC, then the extra time thymocytes spend in the medulla can compensate for their poor performance.…”
Section: Discussionmentioning
confidence: 99%
“…If the increased migration of aPix 2 thymocytes results in inefficient, error-prone scanning for pMHC, then the extra time thymocytes spend in the medulla can compensate for their poor performance. In addition, self-peptides in the medulla induce repeated encounters between thymocytes and mTECs and DCs in confined areas (33), which might ensure that aPix 2 thymocytes would eventually encounter any autoactivating peptides. The normal negative selection we observed in the aPix 2 thymus was supported by a lack of evidence of autoimmune disease in these mice, in contrast to CCR7 knockout mice that exhibit extensive autoimmune pathologies (35).…”
Section: Discussionmentioning
confidence: 99%
“…One of the central questions in this field is whether migration is best described as a (persistent) random walk or whether directed or confined migration is involved, because this is important for our understanding of how cells manage to carry out their functions. Examples of persistent random walk include the migration of T cells, B cells, and plasma cells in lymph nodes (2, 6-8) and of effector T cells migrating in tumors (9), whereas nonrandom migration has for instance been discovered in antigen-engaged B cells moving toward the T zone boundary early in a B-cell response (10), CD8 + T cells being attracted toward "licensed" dendritic cells (11)(12)(13)(14), neutrophil movement in skin (15, 16), and during thymocyte maturation (17,18).In some applications, it is controversial whether migration is best described as random or not, and a prime example is B-cell migration in germinal centers (GCs). At these sites, B lymphocytes mature by somatic hypermutation and clonal selection of the mutants that produce antibody of high affinity.…”
mentioning
confidence: 99%